Learning Styles of Grade 1 Learners in the Public Schools: An Input to Proposed Intervention Measures - Asuncion, Jomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the learning styles of Grade 1 learners in the public elementary schools of Tubao District, Division of La Union, and developed intervention measures to enhance these learning styles. Anchored on the view that learning styles provide a framework for understanding learners’ preferences to support differentiated instructional planning, the study employed a descriptive research design. Data were collected using researcher-constructed questionnaires administered to 25 Grade 1 teachers and 100 parents selected through quota sampling. The instrument was validated through pre-testing and demonstrated high internal consistency reliability (Cronbach’s alpha = 0.89). Frequency counts, percentages, weighted means, and rankings were used to analyze the data. The findings revealed that the learners’ learning styles were overall highly manifested, with visual and mathematical learning styles showing the highest levels of manifestation. Home environment and family support emerged as the most influential factors affecting learning styles, followed by teachers’ instructional strategies and the availability of learning resources. Learning styles were found to contribute greatly to learners’ holistic development, particularly cognitive development. The proposed enhancement measures, especially the use of varied instructional materials and differentiated instruction, were considered highly applicable. The study concludes that recognizing and addressing diverse learning styles through learner-centered instructional practices, strengthened home-school partnerships, and teacher professional development can support the holistic development of Grade 1 learners. The study aligns with Sustainable Development Goal 4 (Quality Education) by promoting inclusive, equitable, and learner-centered educational practices. Its findings contribute to educational, institutional, and socio-economic sustainability by providing evidence that supports responsive instruction, effective resource utilization, and improved learning opportunities for young learners.